A high dielectric constant and high average power microwave ferrite material and preparation method thereof

Through the combination of simulated genetic optimization algorithm and multifunctional additives, combined with sol-gel method and microwave sintering technology, the problems of low dielectric constant and insufficient stability of existing ferrite materials are solved, and high efficiency preparation of high dielectric constants is achieved High average power microwave ferrite material to meet the needs of high-performance electronic components.

CN118255582BActive Publication Date: 2024-12-17DONGYANG FIRST MAGNETICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410202071.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-23
Publication Date
2024-12-17
Estimated Expiration
2044-02-23

AI Technical Summary

Technical Problem

The dielectric constant and magnetic permeability of existing ferrite materials are low, which cannot meet the needs of high-performance electronic components. The traditional preparation methods are inefficient and difficult to control the microstructure and chemical composition of the material, resulting in material uniformity and stability. insufficient.

Method used

The simulated genetic optimization algorithm is used to adjust the proportion of ferrite raw materials, introduce a variety of functional additives and rare earth elements, and control the microstructure and crystal structure of the material through sol-gel method and microwave sintering technology, improve the dielectric constant and saturated magnetic induction of the material. Strength and loss resistance.

Benefits of technology

It significantly improves the performance and preparation efficiency of ferrite materials, meets the application needs in the fields of high dielectric constant and high average power microwaves, improves the uniformity and stability of the materials, and avoids the defects of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118255582B_ABST
    Figure CN118255582B_ABST
Patent Text Reader

Abstract

The invention discloses a high-dielectric-constant high-average-power microwave ferrite material and a preparation method thereof, relates to the field of material science, and solves the problem that the traditional material and the preparation method thereof require high test and time costs, low efficiency, limitations and low quality. The material comprises a ferrite raw material, a ferrite crystal filler, a functional additive, a rare earth element and a preparation solvent. The weight proportions of the components of the ferrite material include 40-70 parts of the ferrite raw material, 5-30 parts of the ferrite crystal filler, 3-10 parts of the functional additive, 0.5-5 parts of the rare earth element and 10-30 parts of the preparation solvent. The invention can control not only the chemical composition and crystal structure of the material, but also the microstructure and morphology of the material, thereby improving the uniformity and stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material science, and more specifically to a high dielectric constant and high average power microwave ferrite material and a preparation method thereof. Background Art

[0002] Ferrite material is a functional ceramic material with excellent electrical, magnetic and thermal properties, and has a wide range of application prospects. Ferrite material with high dielectric constant is an important electronic component material used to make microwave devices and device components. It has a wide range of applications in the fields of electronic communications, radio, radar and microwave technology, such as high-frequency capacitors, microwave filters, antennas, etc. At present, most ferrite materials on the market have low dielectric constants and magnetic permeabilities, which cannot meet the requirements of high-performance electronic components. Therefore, the research and development of a high dielectric constant and high average power microwave ferrite material is of great significance.

[0003] There are many existing methods for preparing high dielectric constant and high average power microwave ferrite materials. The traditional trial and error method requires high testing and time costs and is inefficient; a single additive has limitations in adjusting the performance of ferrite materials; traditional preparation methods are difficult to meet the application requirements of high dielectric constant and high average power microwave fields; the traditional sol-gel method cannot control the microstructure and morphology of ferrite materials, and has defects in material uniformity and stability; the traditional sintering method is difficult to control the crystal structure and chemical composition of the material.

[0004] Therefore, the present invention discloses a high dielectric constant and high average power microwave ferrite material and a preparation method thereof, which can solve the limitations and disadvantages of the above traditional methods. The method uses a variety of additives and powder raw materials, and prepares a ferrite material with high dielectric constant and high average power microwave performance through a specific ratio and processing technology. The method can not only control the chemical composition and crystal structure of the material, but also control the microstructure and morphology of the material, thereby improving the uniformity and stability of the material. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention discloses a high-dielectric constant and high-average-power microwave ferrite material and a preparation method thereof. By introducing a variety of advanced technical means, the performance and preparation efficiency of the ferrite material are effectively improved; a simulated genetic optimization algorithm is adopted to adjust the proportion of ferrite raw materials, which effectively avoids a large number of experiments and time costs required by a traditional trial and error method; a variety of functional additives are introduced to adjust the process performance of the ferrite material, which effectively improves the performance and stability of the material and avoids the limitations of a single additive; rare earth elements are introduced as additives to improve the dielectric constant, saturation magnetic induction intensity and anti-loss performance of the ferrite material, thereby meeting the application requirements in the field of high dielectric constant and high average-power microwaves; a sol-gel method is used to prepare the ferrite material, which can control its microstructure and morphology, improve the uniformity and stability of the material, and avoid the defects and non-uniformity caused by the traditional drying method; and by controlling the sintering atmosphere environment, the crystal structure and chemical composition of the ferrite material can be further adjusted, thereby optimizing its performance and avoiding the limitations of the traditional sintering method that are difficult to control.

[0006] The present invention adopts the following technical solutions:

[0007] A high dielectric constant and high average power microwave ferrite material, the ferrite material comprising:

[0008] A ferrite raw material, used to form a ferrite crystal structure, wherein the ferrite raw material comprises iron oxide, ferrous oxide and iron oxide spinel ferrite powder, wherein the amount of ferrous oxide added is proportional to the loss resistance of the ferrite material, and the amount of ferrous oxide added is inversely proportional to the saturation magnetic induction intensity of the ferrite material, and the ferrite raw material obtains the optimal target addition range of ferrous oxide by simulating a genetic optimization algorithm;

[0009] A ferrite crystal filler, used to improve the grain size uniformity and crystal orientation of the ferrite material, wherein the ferrite crystal filler comprises aluminum oxide, titanium oxide, silicon dioxide, calcium carbonate and silicon carbide, wherein the aluminum oxide accounts for 10-40% of the ferrite crystal filler, the titanium oxide accounts for 0-20% of the ferrite crystal filler, the silicon dioxide accounts for 20-50% of the ferrite crystal filler, the calcium carbonate accounts for 10-40% of the ferrite crystal filler, and the silicon carbide accounts for 10-30% of the ferrite crystal filler;

[0010] Functional additives, used to adjust the process properties of the ferrite material, the functional additives include loss reducing agents, stabilizers, composite reinforcing agents, sintering aids, modifiers, surface modifiers and structure control agents, the loss reducing agents account for 5-25% of the functional additive components, the stabilizers account for 1-5% of the functional additive components, the composite reinforcing agents account for 10-30% of the functional additive components, the sintering aids account for 0.1-3% of the functional additive components, the modifiers account for 3-10% of the functional additive components, the surface modifiers account for 1-10% of the functional additive components, and the structure control agents account for 5-20% of the functional additive components;

[0011] Rare earth elements, used to improve the dielectric constant, saturation magnetic induction intensity and anti-loss performance of the ferrite material, the rare earth elements include dysprosium, terbium, gadolinium, lanthanum, cerium, neodymium and promethium, the dysprosium accounts for 10-30% of the rare earth element composition, the terbium accounts for 20-40% of the rare earth element composition, the gadolinium accounts for 5-15% of the rare earth element composition, the lanthanum accounts for 20-35% of the rare earth element composition, the cerium accounts for 5-10% of the rare earth element composition, the neodymium accounts for 1-10% of the rare earth element composition, and the promethium accounts for 1-10% of the rare earth element composition;

[0012] A preparation solvent is used for mixing, kneading, pressing and drying the raw materials. The preparation solvent comprises water, alcohol and ketone, wherein the water accounts for 45-75% of the preparation solvent components, the alcohol accounts for 15-40% of the preparation solvent components, and the ketone accounts for 10-30% of the preparation solvent components.

[0013] As a further technical solution of the present invention, the simulated genetic optimization algorithm calculates the optimal addition ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder by calculating the fitness function, and the set of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder ratio samples is D=(D 1 ,D 2 ,...,D j ,...,D m ), the anti-loss index value set of the ferrite material corresponding to the proportional sample is X=(x 1 ,x 2 ,...,x j ,...,x m ), m is the number of proportional samples, j is the ordinal number of proportional samples, and the fitness function calculation formula for anti-loss is:

[0014]

[0015] In formula (1), f(X) is the fitness function of anti-loss, x j is the anti-loss index value of the ferrite material corresponding to the jth proportion in the proportion sample, max(X) and min(X) are the maximum and minimum values ​​of the anti-loss index corresponding to the sample set D, respectively. The fitness adjustment error value representing the loss resistance, w 1 is the weight coefficient of the loss resistance index; the index value set of the ferrite material corresponding to the proportional sample is Y=(y 1 ,y 2 ,...,y j ,...,y m ), the fitness function calculation formula of saturation magnetic induction intensity is:

[0016]

[0017] In formula (2), f(Y) is the fitness function of the saturation magnetic induction intensity, y j is the saturation magnetic flux density index value of the ferrite material corresponding to the jth proportion in the proportion sample, max(Y) and min(Y) are the maximum and minimum values ​​of the saturation magnetic flux density index corresponding to the sample set D, respectively. Indicates the fitness adjustment error value of the saturation magnetic induction intensity, w 2 is the weight coefficient of the saturation magnetic induction intensity index; the proportion of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder sample D j The empirical entropy output function formula is:

[0018]

[0019] In formula (3), H(D j ) is the ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder sample D j empirical entropy; comprehensive anti-loss index, saturation magnetic induction intensity and empirical entropy index, the comprehensive fitness function expression of the ferrite material is:

[0020] F=H(D j )[w 1 *|f(X)-f'(X)| / f(X)+w 2 *|f(Y)-f'(Y)| / f(Y)] (4)

[0021] In formula (4), F is the comprehensive fitness function of the ferrite material, f'(X) and f'(Y) are the loss resistance and saturation magnetic induction intensity of the ferrite material obtained at the current addition ratio, and when the comprehensive fitness function value of the ferrite material is the largest, the ratio sample of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder is the optimal addition ratio.

[0022] As a further technical solution of the present invention, the iron oxide accounts for 75-95% of the ferrite raw material components, the ferrous oxide content accounts for 5-25% of the ferrite raw material components, and the iron oxide spinel ferrite powder content accounts for 1.5-3% of the ferrite raw material components.

[0023] As a further technical solution of the present invention, the loss reducing agent includes magnesium ferrite, magnesium oxide, manganese oxide and metal powder, the stabilizer includes calcium oxide, magnesium oxide and zirconium oxide, the composite reinforcing agent includes carbon nanotubes, nano metal particles, nano oxides and nano ferromagnetic oxides, the sintering aid includes sodium carbonate, sodium nitrate, aluminum nitrate and calcium carbonate, the modifier includes silicic acid, aluminum oxide, copper oxide, nickel oxide and zinc oxide, the surface modifier includes organic acid, organic alcohol, phosphate and silane, and the structure control agent includes polyethylene glycol and polyacrylic acid.

[0024] As a further technical solution of the present invention, the components of the ferrite material include 40-70 parts by weight of the ferrite raw material, 5-30 parts of the ferrite crystal filler, 3-10 parts of the functional additive, 0.5-5 parts of the rare earth element, and 10-30 parts of the preparation solvent.

[0025] As a further technical solution of the present invention, a method for preparing a high dielectric constant and high average power microwave ferrite material comprises the following steps:

[0026] Step 1, preparing the ferrite raw material, adjusting the ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder by the simulated genetic optimization algorithm, and adding the iron oxide, ferrous oxide and iron oxide spinel ferrite powder according to the calculated ratio into an automatic heating stirring reactor and stirring and mixing them evenly;

[0027] Step 2: forming a granular material, adding the ferrite crystal filler and the preparation solvent to the mixture of the ferrite raw material and stirring them fully to form a granular material, wherein the particle size of the granular material is less than 20 mm, and adding the loss reducing agent, stabilizer, composite reinforcing agent, modifier and structure control agent during the stirring process to improve the performance of the ferrite material;

[0028] Step 3: forming a composite material, adding the rare earth element to the granular material to form a composite material, wherein the rare earth element changes the crystal structure and chemical composition of the ferrite material through mechanical alloying treatment, and the mechanical alloying treatment adjusts the microstructure through high-speed rotation, friction and collision of powder;

[0029] Step 4, preparing the ferrite material, the composite material adopts the sol-gel method to prepare the ferrite material, the composite material is added to the preparation solvent for sufficient stirring and ultrasonic treatment, and a reducing agent and a precipitating agent are added during the stirring process to form a mixed colloidal solution, the reducing agent includes acetic acid and ethylene glycol, the precipitating agent is ammonia water, the ratio of the added amount of the reducing agent to the composite material is 1:10-1:20, and the ratio of the added amount of the precipitating agent to the composite material is 1:2-1:10, the mixed colloidal solution is fully stirred and heated to dissolve to form an oxidized slurry, the heating temperature is 150°C-200°C, the heating time is 15-30min, the oxidized slurry is cooled to room temperature to form a gel-like ferrite material;

[0030] Step 5: prepare the high dielectric constant and high average power microwave ferrite material, pour the ferrite material into a mold for pressing, and add the pressed ferrite material to the automatic heating and stirring reactor for microwave sintering. The sintering temperature is 1000-1100°C and the sintering time is 1-2h. During the sintering process, the automatic heating and stirring reactor adjusts the atmosphere by controlling the opening and closing of the vent and the exhaust port, and adds the sintering aid and surface modifier.

[0031] As a further technical solution of the present invention, the automatic heating and stirring reactor includes a high-frequency heater, a material tank, a temperature sensor, a PID controller, an agitator, a vent and a discharge port, the high-frequency heater is located at the periphery of the material tank, the high-frequency heater uses microwave heating, the material tank is located in the center of the automatic heating and stirring reactor, the temperature sensor is located at the bottom and side of the material tank, the PID controller is connected to the temperature sensor, the agitator is located in the center of the material tank, the agitator includes a motor, a rotor and a stirring blade, the vent is located at the top of the material tank, and the discharge port is located at the bottom of the material tank.

[0032] Positive beneficial effects:

[0033] The invention discloses a high-dielectric constant and high-average-power microwave ferrite material and a preparation method thereof. The performance and preparation efficiency of the ferrite material are effectively improved by introducing a variety of advanced technical means; a simulated genetic optimization algorithm is adopted to adjust the proportion of ferrite raw materials, effectively avoiding a large number of experiments and time costs required by a traditional trial and error method; a variety of functional additives are introduced to adjust the process performance of the ferrite material, effectively improving the performance and stability of the material, avoiding the limitation of a single additive; rare earth elements are introduced as additives, which can improve the dielectric constant, saturation magnetic induction intensity and anti-loss performance of the ferrite material, thereby meeting the application requirements in the field of high dielectric constant and high average-power microwaves; a sol-gel method is used to prepare the ferrite material, which can control its microstructure and morphology, improve the uniformity and stability of the material, and avoid the defects and non-uniformity brought by the traditional drying method; and the crystal structure and chemical composition of the ferrite material can be further adjusted by controlling the sintering atmosphere environment, thereby optimizing its performance, avoiding the limitation of the traditional sintering method that is difficult to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of the weight percentages of components of a high dielectric constant and high average power microwave ferrite material of the present invention;

[0035] Figure 2 It is a schematic diagram of the content ratio of ferrite crystal filler in a high dielectric constant and high average power microwave ferrite material of the present invention;

[0036] Figure 3 This is a schematic diagram of the content ratio of functional additives in a high dielectric constant and high average power microwave ferrite material of the present invention;

[0037] Figure 4 A schematic diagram of the content ratio of rare earth elements in a high dielectric constant and high average power microwave ferrite material of the present invention;

[0038] Figure 5 A schematic diagram of the proportion of the solvent content in the preparation of a high dielectric constant and high average power microwave ferrite material of the present invention;

[0039] Figure 6 A schematic diagram of the proportion of ferrite raw materials in a high dielectric constant and high average power microwave ferrite material of the present invention;

[0040] Figure 7 A schematic flow chart of a method for preparing a high dielectric constant and high average power microwave ferrite material according to the present invention. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] A high dielectric constant and high average power microwave ferrite material, the ferrite material comprising:

[0044] A ferrite raw material, used to form a ferrite crystal structure, wherein the ferrite raw material comprises iron oxide, ferrous oxide and iron oxide spinel ferrite powder, wherein the amount of ferrous oxide added is proportional to the loss resistance of the ferrite material, and the amount of ferrous oxide added is inversely proportional to the saturation magnetic induction intensity of the ferrite material, and the ferrite raw material obtains the optimal target addition range of ferrous oxide by simulating a genetic optimization algorithm;

[0045] A ferrite crystal filler, used to improve the grain size uniformity and crystal orientation of the ferrite material, wherein the ferrite crystal filler comprises aluminum oxide, titanium oxide, silicon dioxide, calcium carbonate and silicon carbide, wherein the aluminum oxide accounts for 10% of the ferrite crystal filler, the titanium oxide accounts for 0% of the ferrite crystal filler, the silicon dioxide accounts for 20% of the ferrite crystal filler, the calcium carbonate accounts for 10% of the ferrite crystal filler, and the silicon carbide accounts for 10% of the ferrite crystal filler;

[0046] Functional additives, used to adjust the process performance of the ferrite material, the functional additives include loss reducing agent, stabilizer, composite reinforcing agent, sintering aid, modifier, surface modifier and structure control agent, the loss reducing agent accounts for 5% of the functional additive component, the stabilizer accounts for 1% of the functional additive component, the composite reinforcing agent accounts for 10% of the functional additive component, the sintering aid accounts for 0.1% of the functional additive component, the modifier accounts for 3% of the functional additive component, the surface modifier accounts for 1% of the functional additive component, and the structure control agent accounts for 5% of the functional additive component;

[0047] Rare earth elements, used to improve the dielectric constant, saturation magnetic induction intensity and anti-loss performance of the ferrite material, the rare earth elements include dysprosium, terbium, gadolinium, lanthanum, cerium, neodymium and promethium, the dysprosium accounts for 10% of the rare earth element composition, the terbium accounts for 20% of the rare earth element composition, the gadolinium accounts for 5% of the rare earth element composition, the lanthanum accounts for 20% of the rare earth element composition, the cerium accounts for 5% of the rare earth element composition, the neodymium accounts for 1% of the rare earth element composition, and the promethium accounts for 1% of the rare earth element composition;

[0048] A preparation solvent is used for mixing, kneading, pressing and drying the raw materials, wherein the preparation solvent comprises water, alcohol and ketone, wherein the water accounts for 45% of the preparation solvent components, the alcohol accounts for 15% of the preparation solvent components, and the ketone accounts for 10% of the preparation solvent components.

[0049] Through the above formula, an example is now described. A high dielectric constant and high average power microwave ferrite material and a traditional ferrite material made by the above formula are used to make circuits, and comparative tests are performed. Prepare high dielectric constant ferrite samples and traditional ferrite samples. Prepare cut-angle capacitors with the same size as the samples, and insert the samples into the cut-angle capacitors respectively. Connect the cut-angle capacitors to the sweep source and the network analyzer, start the test, and scan the frequency range between 2GHz-10GHz. Record the changes in capacitance and dielectric constant of the two samples with frequency, and record them in Table 1.

[0050] Table 1 Comparative statistics

[0051]

[0052] It is obvious from the above test data that the capacitance value of the high dielectric constant ferrite material made by the above formula is significantly higher than that of the traditional ferrite material at the same frequency, and the dielectric constant is also significantly higher. This shows that the high dielectric constant ferrite material has better microwave communication performance and is suitable for high-speed, high-power and high-frequency microwave communication applications.

[0053] Example 2

[0054] A high dielectric constant and high average power microwave ferrite material, the ferrite material comprising:

[0055] A ferrite raw material, used to form a ferrite crystal structure, wherein the ferrite raw material comprises iron oxide, ferrous oxide and iron oxide spinel ferrite powder, wherein the amount of ferrous oxide added is proportional to the loss resistance of the ferrite material, and the amount of ferrous oxide added is inversely proportional to the saturation magnetic induction intensity of the ferrite material, and the ferrite raw material obtains the optimal target addition range of ferrous oxide by simulating a genetic optimization algorithm;

[0056] A ferrite crystal filler, used to improve the grain size uniformity and crystal orientation of the ferrite material, wherein the ferrite crystal filler comprises aluminum oxide, titanium oxide, silicon dioxide, calcium carbonate and silicon carbide, wherein the aluminum oxide accounts for 40% of the ferrite crystal filler, the titanium oxide accounts for 20% of the ferrite crystal filler, the silicon dioxide accounts for 50% of the ferrite crystal filler, the calcium carbonate accounts for 40% of the ferrite crystal filler, and the silicon carbide accounts for 30% of the ferrite crystal filler;

[0057] Functional additives, used to adjust the process properties of the ferrite material, the functional additives include loss reducing agents, stabilizers, composite reinforcing agents, sintering aids, modifiers, surface modifiers and structure control agents, the loss reducing agents account for 25% of the functional additive components, the stabilizers account for 5% of the functional additive components, the composite reinforcing agents account for 30% of the functional additive components, the sintering aids account for 3% of the functional additive components, the modifiers account for 10% of the functional additive components, the surface modifiers account for 10% of the functional additive components, and the structure control agents account for 20% of the functional additive components;

[0058] Rare earth elements, used to improve the dielectric constant, saturation magnetic induction intensity and anti-loss performance of the ferrite material, the rare earth elements include dysprosium, terbium, gadolinium, lanthanum, cerium, neodymium and promethium, the dysprosium accounts for 30% of the rare earth element composition, the terbium accounts for 40% of the rare earth element composition, the gadolinium accounts for 15% of the rare earth element composition, the lanthanum accounts for 35% of the rare earth element composition, the cerium accounts for 10% of the rare earth element composition, the neodymium accounts for 10% of the rare earth element composition, and the promethium accounts for 10% of the rare earth element composition;

[0059] A preparation solvent is used for mixing, kneading, pressing and drying the raw materials, wherein the preparation solvent comprises water, alcohol and ketone, wherein the water accounts for 75% of the preparation solvent components, the alcohol accounts for 40% of the preparation solvent components, and the ketone accounts for 30% of the preparation solvent components.

[0060] Through the above formula, an example is now described. A high dielectric constant and high average power microwave ferrite material (Group A) and a traditional ferrite material (Group B) made by the above formula are used to make circuits, and comparative tests are performed. Prepare high dielectric constant ferrite samples and traditional ferrite samples. Prepare cut-angle capacitors with the same size as the samples, and insert the samples into the cut-angle capacitors respectively. Connect the cut-angle capacitors to the sweep source and the network analyzer, start the test, and scan the frequency range between 2GHz-10GHz. Record the changes in capacitance and dielectric constant of the two samples with frequency, and record them in Table 2.

[0061] Table 2 Comparative statistics

[0062]

[0063] It is obvious from the above test data that the capacitance value of the high dielectric constant ferrite material made by the above formula is significantly higher than that of the traditional ferrite material at the same frequency, and the dielectric constant is also significantly higher. This shows that the high dielectric constant ferrite material has better microwave communication performance and is suitable for high-speed, high-power and high-frequency microwave communication applications.

[0064] Example 3

[0065] In the above embodiment, the simulated genetic optimization algorithm calculates the optimal addition ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder by calculating the fitness function, and the set of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder ratio samples is D=(D 1 ,D 2 ,...,D j ,...,D m ), the anti-loss index value set of the ferrite material corresponding to the proportional sample is X=(x 1 ,x 2 ,...,x j ,...,x m ), m is the number of proportional samples, j is the ordinal number of proportional samples, and the fitness function calculation formula for anti-loss is:

[0066]

[0067] In formula (1), f(X) is the fitness function of anti-loss, x j is the anti-loss index value of the ferrite material corresponding to the jth proportion in the proportion sample, max(X) and min(X) are the maximum and minimum values ​​of the anti-loss index corresponding to the sample set D, respectively. The fitness adjustment error value representing the loss resistance, w 1is the weight coefficient of the loss resistance index; the index value set of the ferrite material corresponding to the proportional sample is Y=(y 1 ,y 2 ,...,y j ,...,y m ), the fitness function calculation formula of saturation magnetic induction intensity is:

[0068]

[0069] In formula (2), f(Y) is the fitness function of the saturation magnetic induction intensity, y j is the saturation magnetic flux density index value of the ferrite material corresponding to the jth proportion in the proportion sample, max(Y) and min(Y) are the maximum and minimum values ​​of the saturation magnetic flux density index corresponding to the sample set D, respectively. Indicates the fitness adjustment error value of the saturation magnetic induction intensity, w 2 is the weight coefficient of the saturation magnetic induction intensity index; the proportion of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder sample D j The empirical entropy output function formula is:

[0070]

[0071] In formula (3), H(D j ) is the ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder sample D j empirical entropy; comprehensive anti-loss index, saturation magnetic induction intensity and empirical entropy index, the comprehensive fitness function expression of the ferrite material is:

[0072] F=H(D j )[w 1 *|f(X)-f'(X)| / f(X)+w 2 *|f(Y)-f'(Y)| / f(Y)] (4)

[0073] In formula (4), F is the comprehensive fitness function of the ferrite material, f'(X) and f'(Y) are the loss resistance and saturation magnetic induction intensity of the ferrite material obtained at the current addition ratio, and when the comprehensive fitness function value of the ferrite material is the largest, the ratio sample of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder is the optimal addition ratio.

[0074] In a specific embodiment, the simulated genetic optimization algorithm is an optimization algorithm based on the principle of biological evolution, which continuously optimizes the process of solving the objective function by simulating operations such as inheritance, crossover and mutation in nature. In this embodiment, the simulated genetic optimization algorithm is used to solve the optimal addition ratio of high dielectric constant and high average power microwave ferrite materials. According to indicators such as loss resistance, saturation magnetic induction intensity and empirical entropy of ferrite materials, a comprehensive fitness function formula (Formula 4) is designed. A certain number of proportional samples are randomly generated as the initial population. Each proportional sample consists of three elements, which represent the addition ratios of iron oxide, ferrous oxide and iron oxide spinel ferrite powder respectively. Each proportional sample in the initial population is substituted into the comprehensive fitness function formula (Formula 4) to calculate its fitness value, and sorted from large to small according to the fitness value. The best top 50% proportional samples are selected as the parent generation, and crossover and mutation operations are performed to generate a new generation of offspring. Repeat steps 3-4 until convergence or the preset number of iterations is reached. After the iteration is completed, the one with the largest fitness value among all historical optimal solutions is selected as the optimal addition ratio. In this embodiment, the fitness function adopts a multi-index comprehensive evaluation method, taking into account the anti-loss property, saturation magnetic induction intensity and empirical entropy of ferrite materials. By simulating the genetic optimization algorithm and continuously adjusting the addition ratio, the process of solving the objective function is more efficient and accurate. The hardware working environment of the simulated genetic optimization algorithm includes the following:

[0075] 1. Computer software environment: Computer software suitable for executing simulated genetic optimization algorithms is required, such as MATLAB, Python, etc.

[0076] 2. Hardware environment: Calculations need to be performed on a computer with sufficient computing power, and there needs to be enough storage space to store large amounts of data.

[0077] 3. Database environment: It is necessary to establish a database suitable for storing sample data and calculation results to facilitate data management and analysis.

[0078] 4. Laboratory environment: Laboratory equipment and conditions for preparing ferrite samples are required so that the prepared samples can truly reflect the performance indicators corresponding to the calculated optimal ratio.

[0079] 5. Experimental data collection environment: It is necessary to use test equipment suitable for collecting ferrite performance indicators, such as dielectric constant tester, hysteresis loop tester, etc. At the same time, it is necessary to establish a database suitable for storing test data.

[0080] Five groups of ferrite raw material ratios were designed to prepare corresponding ferrite samples. The samples were measured to obtain their dielectric constant values, which were used as the objective function values. The optimal ferrite raw material ratio was calculated using a simulated genetic algorithm, and new ferrite samples were prepared based on the calculated ratio. The differences in dielectric constants between the experimentally prepared ferrite samples and the calculated optimal ratio ferrite material samples were compared, and statistical analysis was performed and recorded in Table 3.

[0081] Table 3 Comparative statistics

[0082] Number of trials Experimental measurement of dielectric constant Algorithm to calculate dielectric constant 1 200 240 2 180 220 3 220 255 4 190 225 5 210 250

[0083] From the table, we can see that the dielectric constant values ​​of the optimal ratio ferrite samples calculated by the simulated genetic algorithm are all higher than the experimental measured values. This shows that the ferrite raw material ratio obtained by the simulated genetic algorithm can indeed effectively improve the performance of ferrite samples, and this method is also quite different between samples. At the same time, the statistical method can be used to verify the significant difference between the calculated value and the experimental value, and evaluate the reliability and accuracy of the simulated genetic algorithm.

[0084] Example 4

[0085] In the above embodiment, the iron oxide content accounts for 75% of the ferrite raw material components, the ferrous oxide content accounts for 5% of the ferrite raw material components, and the iron oxide spinel ferrite powder content accounts for 1.5% of the ferrite raw material components.

[0086] In the above embodiments, the loss reducer includes magnesium ferrite, magnesium oxide, manganese oxide and metal powder, the stabilizer includes calcium oxide, magnesium oxide and zirconium oxide, the composite reinforcing agent includes carbon nanotubes, nano metal particles, nano oxides and nano ferromagnetic oxides, the sintering aid includes sodium carbonate, sodium nitrate, aluminum nitrate and calcium carbonate, the modifier includes silicic acid, aluminum oxide, copper oxide, nickel oxide and zinc oxide, the surface modifier includes organic acid, organic alcohol, phosphate and silane, and the structure control agent includes polyethylene glycol and polyacrylic acid.

[0087] In the above embodiment, the components of the ferrite material include 40 parts of the ferrite raw material, 5 parts of the ferrite crystal filler, 3 parts of the functional additive, 0.5 parts of the rare earth element, and 10 parts of the preparation solvent in parts by weight.

[0088] Through the above formula, an example is now described, a high dielectric constant and high average power microwave ferrite material (Group A) and a traditional ferrite material (Group B) made by the above formula are used to make circuits, and comparative tests are performed. The two ferrite materials are prepared separately so that they have the same shape and size, and the two ferrite materials are used in microwave communication respectively, and their average power performance is measured. Five groups of experiments are performed and recorded in Table 4.

[0089] Table 4 Comparative statistics

[0090] Number of trials Average power of group A Average power of group B 1 2.9W 1.7W 2 3.1W 1.8W 3 2.8W 1.9W 4 3.0W 1.6W 5 2.9W 1.7W

[0091] As can be seen from the table above, the ferrite material in group A showed higher average power performance in the five experiments, with average power performances of 2.94 W and 1.74 W respectively. This proves that the high dielectric constant and high average power microwave ferrite material described in this article has better performance and can effectively improve the performance in microwave communication.

[0092] Example 5

[0093] In the above embodiment, the iron oxide content accounts for 95% of the ferrite raw material components, the ferrous oxide content accounts for 25% of the ferrite raw material components, and the iron oxide spinel ferrite powder content accounts for 3% of the ferrite raw material components.

[0094] In the above embodiments, the loss reducer includes magnesium ferrite, magnesium oxide, manganese oxide and metal powder, the stabilizer includes calcium oxide, magnesium oxide and zirconium oxide, the composite reinforcing agent includes carbon nanotubes, nano metal particles, nano oxides and nano ferromagnetic oxides, the sintering aid includes sodium carbonate, sodium nitrate, aluminum nitrate and calcium carbonate, the modifier includes silicic acid, aluminum oxide, copper oxide, nickel oxide and zinc oxide, the surface modifier includes organic acid, organic alcohol, phosphate and silane, and the structure control agent includes polyethylene glycol and polyacrylic acid.

[0095] In the above embodiment, the components of the ferrite material include 70 parts of the ferrite raw material, 30 parts of the ferrite crystal filler, 10 parts of the functional additive, 5 parts of the rare earth element, and 30 parts of the preparation solvent in parts by weight.

[0096] By the above formula, an example is now described, a high dielectric constant and high average power microwave ferrite material (Group A) and a traditional ferrite material (Group B) made by the above formula are used to make circuits, and comparative tests are performed. The two ferrite materials are prepared separately so that they have the same shape and size, and the two ferrite materials are used in microwave communication respectively, and their average power performance is measured. Five groups of experiments are performed and recorded in Table 5.

[0097] Table 5 Comparative statistics

[0098] Number of trials Average power of group A Average power of group B 1 3.1W 1.7W 2 3.3W 1.8W 3 3.0W 1.9W 4 3.2W 1.6W 5 3.1W 1.7W

[0099] As can be seen from the table above, the ferrite material in group A showed higher average power performance in the five experiments, with average power performances of 3.14 W and 1.74 W respectively. This proves that the high dielectric constant and high average power microwave ferrite material described in this article has better performance and can effectively improve the performance in microwave communication.

[0100] Example 6

[0101] In the above embodiment, a method for preparing a high dielectric constant and high average power microwave ferrite material comprises the following steps:

[0102] Step 1, preparing the ferrite raw material, adjusting the ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder by the simulated genetic optimization algorithm, and adding the iron oxide, ferrous oxide and iron oxide spinel ferrite powder according to the calculated ratio into an automatic heating stirring reactor and stirring and mixing them evenly;

[0103] Step 2: forming a granular material, adding the ferrite crystal filler and the preparation solvent to the mixture of the ferrite raw material and stirring them fully to form a granular material, wherein the particle size of the granular material is less than 20 mm, and adding the loss reducing agent, stabilizer, composite reinforcing agent, modifier and structure control agent during the stirring process to improve the performance of the ferrite material;

[0104] Step 3: forming a composite material, adding the rare earth element to the granular material to form a composite material, wherein the rare earth element changes the crystal structure and chemical composition of the ferrite material through mechanical alloying treatment, and the mechanical alloying treatment adjusts the microstructure through high-speed rotation, friction and collision of powder;

[0105] Step 4: prepare the ferrite material. The composite material is prepared by a sol-gel method. The composite material is added to the preparation solvent for sufficient stirring and ultrasonic treatment. During the stirring process, a reducing agent and a precipitating agent are added to form a mixed colloidal solution. The reducing agent includes acetic acid and ethylene glycol, and the precipitating agent is aqueous ammonia. The ratio of the amount of the reducing agent added to the composite material is 1:10, and the ratio of the amount of the precipitating agent added to the composite material is 1:2. The mixed colloidal solution is fully stirred and heated to dissolve to form an oxidized slurry. The heating temperature is 150°C and the heating time is 15 minutes. The oxidized slurry is cooled to room temperature to form a gel-like ferrite material.

[0106] Step 5: prepare the high dielectric constant and high average power microwave ferrite material, pour the ferrite material into a mold for pressing, and add the pressed ferrite material to the automatic heating and stirring reactor for microwave sintering. The sintering temperature is 1000°C and the sintering time is 1 hour. During the sintering process, the automatic heating and stirring reactor adjusts the atmosphere by controlling the opening and closing of the vent and the exhaust port, and adds the sintering aid and surface modifier.

[0107] Through the above-mentioned preparation method, an example is now described, and a circuit is made using a high dielectric constant and high average power microwave ferrite material (Group A) and a traditional ferrite material (Group B) prepared by the above-mentioned preparation method, and a comparative test is performed. The two ferrite materials are prepared separately so that they have the same shape and size, and the dielectric constant, average power, hysteresis loop and microwave power bearing capacity of the two ferrite materials are measured and recorded in Table 6.

[0108] Table 6 Comparative statistics

[0109] Performance Indicators Group A Group B Dielectric constant 13.6 9.8 Hysteresis loop 0.034 0.048 Microwave power handling capability 3.2W 2.1W Average power performance 2.8W 1.8W

[0110] As can be seen from the table above, group A ferrite materials have higher dielectric constants, smaller hysteresis loops, and higher microwave power tolerance, and have higher performance in microwave communication applications. At the same time, the average power performance of group A ferrite materials is also significantly higher than that of group B ferrite materials, proving that the high dielectric constant and high average power microwave ferrite materials described in this article have good performance advantages and can effectively improve the performance in microwave communications.

[0111] Example 7

[0112] In the above embodiment, a method for preparing a high dielectric constant and high average power microwave ferrite material comprises the following steps:

[0113] Step 1, preparing the ferrite raw material, adjusting the ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder by the simulated genetic optimization algorithm, and adding the iron oxide, ferrous oxide and iron oxide spinel ferrite powder according to the calculated ratio into an automatic heating stirring reactor and stirring and mixing them evenly;

[0114] Step 2: forming a granular material, adding the ferrite crystal filler and the preparation solvent to the mixture of the ferrite raw material and stirring them fully to form a granular material, wherein the particle size of the granular material is less than 20 mm, and adding the loss reducing agent, stabilizer, composite reinforcing agent, modifier and structure control agent during the stirring process to improve the performance of the ferrite material;

[0115] Step 3: forming a composite material, adding the rare earth element to the granular material to form a composite material, wherein the rare earth element changes the crystal structure and chemical composition of the ferrite material through mechanical alloying treatment, and the mechanical alloying treatment adjusts the microstructure through high-speed rotation, friction and collision of powder;

[0116] Step 4: prepare the ferrite material. The composite material is prepared by a sol-gel method. The composite material is added to the preparation solvent for sufficient stirring and ultrasonic treatment. During the stirring process, a reducing agent and a precipitating agent are added to form a mixed colloidal solution. The reducing agent includes acetic acid and ethylene glycol, and the precipitating agent is aqueous ammonia. The ratio of the amount of the reducing agent added to the composite material is 1:20, and the ratio of the amount of the precipitating agent added to the composite material is 1:10. The mixed colloidal solution is fully stirred and heated to dissolve to form an oxidized slurry. The heating temperature is 200°C and the heating time is 30 minutes. The oxidized slurry is cooled to room temperature to form a gel-like ferrite material.

[0117] Step 5: prepare the high dielectric constant and high average power microwave ferrite material, pour the ferrite material into a mold for pressing, and add the pressed ferrite material to the automatic heating and stirring reactor for microwave sintering. The sintering temperature is 1100°C and the sintering time is 2 hours. During the sintering process, the automatic heating and stirring reactor adjusts the atmosphere by controlling the opening and closing of the vent and the exhaust port, and adds the sintering aid and surface modifier.

[0118] Through the above-mentioned preparation method, an example is now described, and a circuit is made using a high dielectric constant and high average power microwave ferrite material (Group A) and a traditional ferrite material (Group B) prepared by the above-mentioned preparation method, and a comparative test is performed. The two ferrite materials are prepared separately so that they have the same shape and size, and the dielectric constant, average power, hysteresis loop and microwave power bearing capacity of the two ferrite materials are measured and recorded in Table 7.

[0119] Table 7 Comparative statistics

[0120] Performance Indicators Group A Group B Dielectric constant 13.8 9.8 Hysteresis loop 0.032 0.048 Microwave power handling capability 3.4W 2.1W Average power performance 3.0W 1.8W

[0121] As can be seen from the table above, group A ferrite materials have higher dielectric constants, smaller hysteresis loops, and higher microwave power tolerance, and have higher performance in microwave communication applications. At the same time, the average power performance of group A ferrite materials is also significantly higher than that of group B ferrite materials, proving that the high dielectric constant and high average power microwave ferrite materials described in this article have good performance advantages and can effectively improve the performance in microwave communications.

[0122] In the above embodiment, the automatic heating and stirring reactor includes a high-frequency heater, a material tank, a temperature sensor, a PID controller, an agitator, a vent and a discharge port, the high-frequency heater is located at the periphery of the material tank, the high-frequency heater uses microwave heating, the material tank is located in the center of the automatic heating and stirring reactor, the temperature sensor is located at the bottom and side of the material tank, the PID controller is connected to the temperature sensor, the agitator is located in the center of the material tank, the agitator includes a motor, a rotor and a stirring blade, the vent is located at the top of the material tank, and the discharge port is located at the bottom of the material tank.

[0123] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that these specific embodiments are only illustrative, and those skilled in the art may omit, replace, and change the details of the above methods and systems in various ways without departing from the principles and essence of the present invention. For example, merging the above method steps so as to perform substantially the same functions in substantially the same manner to achieve substantially the same results is within the scope of the present invention. Therefore, the scope of the present invention is limited only by the appended claims.

Claims

1. A high dielectric constant and high average power microwave ferrite material, characterized in that: The ferrite material comprises: A ferrite raw material, used to form a ferrite crystal structure, wherein the ferrite raw material comprises iron oxide, ferrous oxide and iron oxide spinel ferrite powder, wherein the amount of ferrous oxide added is proportional to the loss resistance of the ferrite material, and the amount of ferrous oxide added is inversely proportional to the saturation magnetic induction intensity of the ferrite material, and the ferrite raw material obtains the optimal target addition range of ferrous oxide by simulating a genetic optimization algorithm; A ferrite crystal filler, used to improve the grain size uniformity and crystal orientation of the ferrite material, wherein the ferrite crystal filler comprises aluminum oxide, titanium oxide, silicon dioxide, calcium carbonate and silicon carbide, wherein the aluminum oxide accounts for 10-40% of the ferrite crystal filler, the titanium oxide accounts for 0-20% of the ferrite crystal filler, the silicon dioxide accounts for 20-50% of the ferrite crystal filler, the calcium carbonate accounts for 10-40% of the ferrite crystal filler, and the silicon carbide accounts for 10-30% of the ferrite crystal filler; Functional additives, used to adjust the process properties of the ferrite material, the functional additives include loss reducing agents, stabilizers, composite reinforcing agents, sintering aids, modifiers, surface modifiers and structure control agents, the loss reducing agents account for 5-25% of the functional additive components, the stabilizers account for 1-5% of the functional additive components, the composite reinforcing agents account for 10-30% of the functional additive components, the sintering aids account for 0.1-3% of the functional additive components, the modifiers account for 3-10% of the functional additive components, the surface modifiers account for 1-10% of the functional additive components, and the structure control agents account for 5-20% of the functional additive components; Rare earth elements, used to improve the dielectric constant, saturation magnetic induction intensity and anti-loss performance of the ferrite material, the rare earth elements include dysprosium, terbium, gadolinium, lanthanum, cerium, neodymium and promethium, the dysprosium accounts for 10-30% of the rare earth element composition, the terbium accounts for 20-40% of the rare earth element composition, the gadolinium accounts for 5-15% of the rare earth element composition, the lanthanum accounts for 20-35% of the rare earth element composition, the cerium accounts for 5-10% of the rare earth element composition, the neodymium accounts for 1-10% of the rare earth element composition, and the promethium accounts for 1-10% of the rare earth element composition; A preparation solvent is used for mixing, kneading, pressing and drying the raw materials, wherein the preparation solvent comprises water, alcohol and ketone, wherein the water accounts for 45-75% of the preparation solvent components, the alcohol accounts for 15-40% of the preparation solvent components, and the ketone accounts for 10-30% of the preparation solvent components; The simulated genetic optimization algorithm calculates the optimal addition ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder by calculating the fitness function, and the set of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder ratio samples is D=(D1, D2, ..., D j ,...,D m ), the anti-loss index value set of the ferrite material corresponding to the proportional sample is X=(x1,x2,...,x j ,...,x m ), m is the number of proportional samples, j is the ordinal number of proportional samples, and the fitness function calculation formula for anti-loss is: In formula (1), f(X) is the fitness function of anti-loss, x j is the anti-loss index value of the ferrite material corresponding to the jth proportion in the proportion sample, max(X) and min(X) are the maximum and minimum values ​​of the anti-loss index corresponding to the sample set D, respectively. represents the fitness adjustment error value of the anti-loss performance, w1 is the weight coefficient of the anti-loss performance index; the saturation magnetic induction intensity index value set of the ferrite material corresponding to the proportional sample is Y=(y1,y2,...,y j ,...,y m ), the fitness function calculation formula of saturation magnetic induction intensity is: In formula (2), f(Y) is the fitness function of the saturation magnetic induction intensity, y j is the saturation magnetic flux density index value of the ferrite material corresponding to the jth proportion in the proportion sample, max(Y) and min(Y) are the maximum and minimum values ​​of the saturation magnetic flux density index corresponding to the sample set D, respectively. represents the fitness adjustment error value of the saturation magnetic induction intensity, w2 is the weight coefficient of the saturation magnetic induction intensity index; the proportion sample D of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder j The empirical entropy output function formula is: In formula (3), H(D j ) is the ratio of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder sample D j empirical entropy; comprehensive anti-loss index, saturation magnetic induction intensity and empirical entropy index, the comprehensive fitness function expression of the ferrite material is: F=H(D j )[w1*|f(X)-f'(X)| / f(X)+w2*|f(Y)-f'(Y)| / f(Y)] (4) In formula (4), F is the comprehensive fitness function of the ferrite material, f'(X) and f'(Y) The anti-loss property and saturation magnetic induction intensity of the ferrite material obtained under the current addition ratio, when the comprehensive fitness function value of the ferrite material is the maximum, the ratio sample of the iron oxide, ferrous oxide and iron oxide spinel ferrite powder is the optimal addition ratio; The loss reducing agent includes magnesium ferrite, magnesium oxide, manganese oxide and metal powder, the stabilizer includes calcium oxide, magnesium oxide and zirconium oxide, the composite reinforcing agent includes carbon nanotubes, nano metal particles, nano oxides and nano ferromagnetic oxides, the sintering aid includes sodium carbonate, sodium nitrate, aluminum nitrate and calcium carbonate, the modifier includes silicic acid, aluminum oxide, copper oxide, nickel oxide and zinc oxide, the surface modifier includes organic acid, organic alcohol, phosphate and silane, and the structure control agent includes polyethylene glycol and polyacrylic acid; The components of the ferrite material include 40-70 parts of the ferrite raw material, 5-30 parts of the ferrite crystal filler, 3-10 parts of the functional additive, 0.5-5 parts of the rare earth element, and 10-30 parts of the preparation solvent in parts by weight.